Pengaruh Keikutsertaan Program Kampus Mengajar dan Kemampuan Technological Pedagogical Content Knowledge terhadap Kesiapan Menjadi Guru - Qurrotul A’yuni; Nurus Sobakh; Etta Mamang Sangadji (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is grounded in the importance of equipping prospective teachers with professional competencies required in the digital era. The Kampus Mengajar program provides students with practical teaching experiences through direct involvement in schools, while mastery of TPACK is essential for designing instruction that aligns with contemporary educational demands. The purpose of this research is to examine the influence of participation in the Kampus Mengajar program and TPACK mastery on the teaching readiness of students in the Faculty of Pedagogy and Psychology at Universitas PGRI Wiranegara. The study adopts the TPACK framework, which integrates content, pedagogy, and technology. Using a quantitative associative design, the research involved 86 respondents from cohorts 5 to 8 of Kampus Mengajar participants. Data were analyzed through multiple linear regression. The findings indicate that participation in the Kampus Mengajar program has a positive and significant effect on teaching readiness (t = 3.132 > t-table 1.989; sig. = 0.002). Likewise, TPACK mastery significantly influences teaching readiness (t = 8.520; sig. = 0.000). Simultaneously, both variables show a significant effect on teaching readiness (F = 103.752 > F-table 3.105; sig. = 0.000). The study concludes that engagement in Kampus Mengajar and TPACK competence, both individually and jointly, contribute to preparing students for the teaching profession. These results highlight the need for higher education institutions to strengthen practical programs and foster the integration of pedagogy and technology in teacher education.